Предмет: Математика,
автор: Александра0Сокаль
9 (х+1)-2 (2х-3х)=-10
Ответы
Автор ответа:
0
9(х+1)-2(2х-3х)= -10
9х+9-4х-6х= -10
9х-4х-6х=-9-(-10)
-1х=1
х= -1
ответ: -1
Автор ответа:
0
Это не может быть системой, так как в начале такого не проходят)
Автор ответа:
0
9(х+1)-2(2х-3х)=-10
9х+1-4х+6х+10=0
9х-4х+6х=-10-1
11х=-11
Х=-1
9х+1-4х+6х+10=0
9х-4х+6х=-10-1
11х=-11
Х=-1
Похожие вопросы
Предмет: Математика,
автор: lOokskdkp
Предмет: Геометрия,
автор: disbalsnsercoc
Предмет: Литература,
автор: Lolik4324
Предмет: Обществознание,
автор: sollko
Предмет: Математика,
автор: VLADA5551000